Implementation of mechanism of action biology-driven early drug development for children with cancer. (July 2016) - Pearson, Andrew D.J.; Herold, Ralf; Rousseau, Raphaël; Copland, Chris; Bradley-Garelik, Brigid; Binner, Debbie; Capdeville, Renaud; Caron, Hubert; Carleer, Jacqueline; Chesler, Louis; Geoerger, Birgit; Kearns, Pamela; et al.
Abstract: An urgent need remains for new paediatric oncology drugs to cure children who die from cancer and to reduce drug-related sequelae in survivors. In 2007, the European Paediatric Regulation came into law requiring industry to create paediatric drug (all types of medicinal products) development programmes alongside those for adults. Unfortunately, paediatric drug development is still largely centred on adult conditions and not a mechanism of action (MoA)-based model, even though this would be more logical for childhood tumours as these have much fewer non-synonymous coding mutations than adult malignancies. Recent large-scale sequencing by International Genome Consortium and Paediatric Cancer Genome Project has further shown that the genetic and epigenetic repertoire of driver mutations in specific childhood malignancies differs from more common adult-type malignancies. To bring about much needed change, a Paediatric Platform, ACCELERATE, was proposed in 2013 by the Cancer Drug Development Forum, Innovative Therapies for Children with Cancer, the European Network for Cancer Research in Children and Adolescents and the European Society for Paediatric Oncology. The Platform, comprising multiple stakeholders in paediatric oncology, has three working groups, one with responsibility for promoting and developing high-quality MoA-informed paediatric drug development programmes, including specific measures for adolescents. Key is the establishment of a freely accessible aggregated database of paediatric biological tumour drug targets to be aligned with an aggregated pipeline of drugs. This will enable prioritisation and conduct of early phase clinical paediatric trials to evaluate these drugs against promising therapeutic targets and to generate clinical paediatric efficacy and safety data in an accelerated time frame. Through this work, the Platform seeks to ensure that potentially effective drugs, where the MoA is known and thought to be relevant to paediatric malignancies, are evaluated in early phase clinical trials, and that this approach to generate pre-clinical and clinical data is systematically pursued by academia, sponsors, industry, and regulatory bodies to bring new paediatric oncology drugs to front-line therapy more rapidly. Highlights: The need for new drugs for children with cancer is greater than ever. Paediatric drug development still largely centres on adult conditions. A mechanism of action model of drug development is proposed by ACCELERATE. An aggregated paediatric tumour biological database matches the drug pipeline. This new paradigm allows early evaluation of new drugs in children and teenagers.